Presupuesto contable, las ventajas y desventajas en su elaboración e implementación en las diferentes organizaciones privadas (2023)
The purpose of this article is to provide knowledge about what the accounting budget is, and to analyze, from the theory of relativity, the advantages and disadvantages in the development of this valuable and useful tool for the projection and control of business resources; To achieve the objective, the theoretical descriptive documentary methodology was used; The bibliographic design was established by consulting various sources from which pertinent and relevant information on the topic was collected, whose analysis allowed us to establish that the disadvantages or limitations of the accounting budget were known; does not mean that it does not work, on the contrary, they must be observed as strategic points to improve and strengthen its useful function, which requires being prepared, executed and monitored in each of its components and times by qualified personnel, since this entails to corrective implementation, when its readjustment is necessary, in this way, the efficient performance of the accounting budget can be ensured to comply with the purposes, goals, and policies established by the same private organization.